Synergistic activation of bat SARS-like coronaviruses spike protein by elastase and TMPRSS2 - Yuichiro Yamamoto; Tetsuya Inoue; Naoto Sugiyama; Miyu Furukawa; Kaoru Sato; Taishi Onodera; Yoshimasa Takahashi; Takaji Wakita; Masayoshi Fukasawa; Kohji Noguchi (Scientific Reports)
Abstract Although numerous sarbecoviruses have been identified in bats, but most lack the ability to infect human cells. Some barriers limit coronavirus zoonosis, including susceptibility to host proteases. Here, we investigated whether exogenous protease treatment can circumvent host restrictions in two severe acute respiratory syndrome (SARS)-related bat coronaviruses. We found that the spike proteins of RaTG13 and Khosta-2, which are sarbecoviruses obtained from horseshoe bats in China and Russia, respectively, facilitated the ACE2-mediated entry of pseudotyped viruses into VeroE6/TMPRSS2 cells following elastase treatment. In contrast, trypsin and thermolysin exhibited no effects. Elastase-enhanced infectivity correlated with increased fusogenicity driven by the cleavage of spike proteins. This process was TMPRSS2-dependent and was inhibited by nafamostat, a TMPRSS2 inhibitor. Additionally, mutation of residue 809 within the S2 subunit of the RaTG13 spike protein (S809D) impaired elastase-induced cleavage and infectivity. Hence, proteolytic processing of the spike protein serves as a restriction to RaTG13 and Khosta-2 infections, which can be overcome by elastase. This suggests that elastase secreted in inflamed tissues during viral infection may increase the zoonotic potential of sarbecoviruses by facilitating human cell entry.